EFEKTIVITAS MEDIASI DALAM PENCEGAHAN PERCERAIAN DI PENGADILAN AGAMA KELAS 1A KOTA BENGKULU - Wijaya, Agung Supra (UIN Fatmawati Sukarno Bengkulu, 2017)
Researcher discusses the problems effectiveness of mediation in Class 1A Religious Court of Bengkulu. In the first study that has been conducted by researchers at the Class 1A Religious Court of Bengkulu City found information about the low success of the mediation conducted by a judge mediator and the sheer number divorce cases in Class 1A Religious Court of Bengkulu. Based on the description above, the formulation of the problem: How is the effectiveness of mediation in preventing divorce conducted by the Religious Court of Bengkulu City Class 1A. And the factors that become supporting and inhibiting the success of mediation in Class 1A Religious Court of Bengkulu City . In this thesis the author uses the method used in the study of this law is the juridical sociological. Results from this study is the author concluded that the mediation is conducted in the Religious Court of Bengkulu City Class 1A by following the reference of PERMA No.01 of 2008 has not been effective although there are successful but still very low, many factors are the cause of which is the level of compliance in the community through the process of mediation is still very low, culture of people who argue that divorce is not a disgrace to individuals and families and the quality of the judges appointed as a mediator is still uneven and there are only four (6) judges who have attended mediation training organized by the Supreme Court Republic of Indonesia.